Criticism Against Human Rights Violations In C. Hope Flinchbaugh's Novel Daughter Of China (2002) - Purianingtyas, Allen Rufaida; , Dr. M. Thoyibi, M.S; , Dr. Phil. Dewi Candraningrum, M.Ed (2015)
Purianingtyas, Allen Rufaida. S200110034. 2014. Criticism Against Human Rights Violation in C. Hope Flinchbaugh's Novel Daughter of China (2002). Thesis. Magister Program of Language Study. School of Postgraduate. Muhammadiyah University of Surakarta. Advisors: (1) Dr. Moch. Thoyibi,M.S , (2) Dr. Phil. Dewi Candraningrum, M.Ed. This research deals with the following aims: (1) describing the context of Daughter of China, (2) explaining the criticism of the author against violation of human rights, (3) describing the author's evangelical mission. The qualitative research is outlined by the descriptive method. The writer of the thesis collected and categorized the data obtained. The first step was exposing the context of United States of America and People's Republic of China Society at the end of the twentieth century. Then it was followed by the analysis of the author's criticism against human right violation and the author's evangelical mission. The result of this research are as follows: (1) there was correlation between author's social background and intention and the social context of People's Republic of China and United States of America, (2) author's criticism about human rights violation can be categorized into upper class intimidation, social disparity, the rigid government rules which consist of One Child Policy and loyalist communist obligation, gender inequality which consist of abandoned baby girl and attitude toward girls' education, starvation of children's orphanage, the limitation of religious freedom, and the peasants' obligation to the government, (3) The evangelical mission conveyed by the author which had been identified was based on the following principals: (1) faithful, (2) loving and confident, (3) tolerant and respectability, (4) recognizing others, (5) religious freedom, (6) peace, (7) exemplification, and (8) dialogue